Milet, Türkei: Stadt und Statue im spätantiken Kleinasien: Die Faustinathermen in Milet im Übergang von der Kaiserzeit zur Spätantike - Dally, Ortwin; Göçmen, Duygu; Kruip, Margrith; Maischberger, Martin; Schneider, Peter; Scholl, Andreas; Schwerdt, Nico (e-Forschungsberichte des DAI, 2023)
The Baths of Faustina in Miletus are the focus of the research project “City and Statue in Late Antique Asia Minor“. Fieldwork in the areas of the architecture, archaeology and geoarchaeology was conducted from 2006 until 2013 to provide further information on the construction period, building phases, facilities and lifespan of the baths. To follow this objective, pottery is examined for a refined chronological dating of the historical activities at the site. In addition, the restoration of vault and walls of room 14 was finished in 2012.